Points of arrival: travels in time, space, and self = Zielpunkte: Unterwegs in Zeit, Raum und Selbst - Gymnich, Marion; Nünning, Ansgar; Nünning, Vera; Nivre, Elisabeth Wåghäll (A. Francke Verlag, 2007)
The articles in this volume discuss different types of travel and migration narratives written in German, English, French and Spanish from the Early Modern period to the present. Travel and migration narratives are examined with respect to issues that are highly relevant from the point of view of literacy and cultural studies, such as the depiction of encounters between the self and the other, migration and exile, gender and national stereotypes. The authors whose works are discussed include Heinrich Böll, Judith Hermann, Katherine Mansfield, Ruth Klüger and Jean Rhys. Der Sammelband beschäftigt sich mit unterschiedlichsten Ausprägungen der Reise- und Migrationsliteratur. Anhand von Beispielen aus der deutschen, englischen, amerikanischen, französischen und spanischen Literatur von der Frühen Neuzeit bis zur Gegenwart werden aus literatur- und kulturwissenschaftlicher Sicht so relevante Themen wie Begegnungen mit dem Selbst und dem Anderen, Migration und Exil oder auch Gender und Nationalstereotype diskutiert. Zu den Autoren und Autorinnen, deren Werke behandelt werden, zählen Heinrich Böll, Judith Hermann, Katherine Mansfield, Ruth Klüger und Jean Rhys.
Keywords: Konferenzschrift -- 2006 -- Stockholm; Geschichte 1500-2000; Identität; Exil; Migration; Reiseliteratur